Synthesis of multifunctional bioresponsive polymers for the management of chronic wounds1. Issue 5 (30th January 2013) - Nyanhongo, Gibson S.; Sygmund, Christoph; Ludwig, Roland; Prasetyo, Endry Nugroho; Guebitz, Georg M
Abstract: Novel multifunctional bioresponsive gelatin and alginate based hydrogels with in‐built antioxidant regenerating system and antimicrobial properties were successfully synthesized. These hydrogels are based on the versatile reactions catalyzed by cellobiose dehydrogenase (CDH). CDH uses cellobiose and cello‐oligosacharides as electron donors to reduce oxidized phenolic antioxidants, quinones, or molecular oxygen to H2 O2 (a well‐known antimicrobial agent). The antioxidant regenerating system consisting of CDH and cellobiose increased the ability of catechol to quench nitric oxide (NO), superoxide (O2 − ) and hydroxyl radicals (OH ) in solution and when incorporated into hydrogels. The CDH loaded into the hydrogels free of oxidized phenolic antioxidants and quinones reduced molecular to H2 O2 resulting in the complete inhibition of the growth of Stapylococcus aeureus, Bacillus subtilis, Pseudomonas putida, Escherichia coli and Cellulomonasmicrobium cellulans . This study therefore presents a new concept for synthesizing multifunctional bioresponsive chronic wound dressing polymers with in‐built continuous antioxidant system able to continuously quench [reactive oxygen species (ROS) and reactive nitrogen species (RNOS)], and antimicrobial properties able to prevent microbial colonization of wound. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.